Text-book Evaluation Entitled “Let’s Learn English” (K-13 English Text-Book) - Ima Isnaini Taufiqur Rohmah (ETERNAL (English Teaching Journal), 2015)
The main elements of teaching are included teachers, students, and textbooks. Many people argue that the students are the key success of the teaching. Thinking to against that many people belief, many studies pointed the view that textbooks are the key of learning. It based on the assumption that both teacher and students are depend on the book in learning process. Therefore, great care and attention to the quality of text-book itself has to be taken in selecting the most appropriate textbook that fit to some factors as teacher’s interests, teaching objectives and finally students’ needs as well. Textbook evaluation checklist by Daoud and Celce-Murcia (1979) is used in this study because it is most appropriate for evaluating this current textbook. In this current study, the researcher evaluated K-13 English text book used by XII grade students of MAN 1 Bojonegoro as instructional material in the teaching and learning. Some aspects to be evaluated based on Textbook evaluation checklist by Daoud and Celce-Murcia (1979) including subject matter, vocabulary and structures, exercises, illustration, and physical make-up. This study is important as it hope will find out the strength as well as the weaknesses areas of the course book. This current study has been developed in order to analyze an available specialized course book for the second grade students. The results of the current study have important implications both for language teachers and the improvement of the course book